Power System State Estimation with Weighted Linear Least Square - Seyed Mehdi Mahaei; Mohammad Reza Navayi (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Power system state estimation with conventional method, Weighted Linear Least (WLS), is performed in two steps. In the first stage the obsevability of system is done and then is system is observed state estimation is carried out. Otherwise estimator is disrupted and is not able to estimate the states. The another estimator, Weighted least Absolute Value (WLAV) has presented which is  able to estimate the system states in all situations but this estimator have auxiliary variable which reduces the convergence rate estimator. In this paper, a new method, Weighted Linear Least Square (WLLS), is proposed for power system state estimation. The proposed method, WLLS, has fewer variables than WLAV. The objective function of the proposed method is linear therefore this estimator is able to estimate the states in unobservability situations. Case studies on IEEE 14 bus system show WLLS has good accuracy and speed and is able to estimate the states in all conditions.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5874